Exploring the Impact of Teacher-Led Silent Meditation Practices in Buddhist Sunday Schools - I Ketut Damana; Colin Simonds (Universitas Negeri Semarang, 2024)
There is a notable reluctance or uncertainty among practitioners regarding the effective grasp and application of health meditation techniques, which impacts the overall effectiveness of meditation education and potentially hinders the optimization of student learning outcomes in health meditation. This study aims to assess and enhance the effectiveness of teacher education methods in Buddhist Sunday schools, particularly focusing on the impact of these methods on student learning outcomes in health meditation. The research addresses the challenge of reluctance or uncertainty among Buddhist practitioners in grasping and applying health meditation techniques. This study employs a descriptive qualitative approach to provide a comprehensive understanding of the teaching strategies used in health meditation at Vipassana Giri Ratana, Bogor. The methodology encompasses a mix of interviews, observations, and documentation analysis. These methods are chosen to capture a holistic view of the educational practices and the context within which they occur. The primary focus is on the silent education method used by teachers, aiming to explore its effectiveness and impact on student learning. The analytical framework of this research is based on the model proposed, which involves four stages: data collection, data reduction, data display, and conclusion drawing. This framework allows for a systematic and structured analysis of the collected data, ensuring that the findings are robust and credible. Key areas of investigation include the pedagogical content knowledge shared in health meditation, factors influencing the practice of health meditation, and the challenges faced in the implementation of meditation education at Vipassana Giri Ratana, Bogor. The study seeks to provide detailed insights into the nature of health meditation education, including the forms of knowledge imparted and the specific obstacles encountered in practicing meditation education in this context. Through this research, we aim to contribute to the broader understanding of effective teaching strategies in Buddhist educational settings and their impact on student learning outcomes in the field of health meditation.